HYGIENIC FACTORS FOR THE DEVELOPMENT OF PHYSICAL QUALITIES OF CHILDREN IN PRESCHOOL EDUCATION - Achilova Soxiba Xamidovna; Gulomova Dilgira (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes hygienic factors for the development of physical qualities of children in preschool education. It was also mentioned about the methods of physical exercise in the development of physical qualities of preschool children.